The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/sgpe-04-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Student reflections on doctoral learning: challenges and breakthroughs

Abstract: Purpose There has been sustained interest in how to support doctoral students through the often-gruelling journey they undertake from enrolment to graduation. Although doctoral numbers and successful completions have been steadily increasing globally as well as in Australia, the quality of student progression and outcomes has been widely interrogated and criticised in the literature that is reported in this paper. The authors’ interest as experienced research higher degree supervisors and research leaders in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
1
20
0
4
Order By: Relevance
“…Lastly, we complicate the idea of progress in a dissertation and how the pandemic may have helped our participants define what is meaningful to them. Owens et al (2020) found that the 18 doctoral students in their study had trouble managing the relationship with their supervisors, and described students being "at the mercy of a supervisor's career changes, periods of leave, illness, retirement, redundancy and/or death" (p. 113). The pandemic stressed this often precarious relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we complicate the idea of progress in a dissertation and how the pandemic may have helped our participants define what is meaningful to them. Owens et al (2020) found that the 18 doctoral students in their study had trouble managing the relationship with their supervisors, and described students being "at the mercy of a supervisor's career changes, periods of leave, illness, retirement, redundancy and/or death" (p. 113). The pandemic stressed this often precarious relationship.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges may be of a personal nature, including stress (Barry et al, 2018), gender-related issues (Carter et al, 2013;Erichsen et al, 2014), feeling like an imposter (Fernandez et al, 2019), and managing the identity transformation process (Koole & Stack, 2016). There are also academic and institution-based challenges, such as funding (Fernandez et al, 2019), the academic environment (McAlpine, 2017), and managing relationships between the advisor and the advisee (Owens et al, 2020). Together, these challenges on a personal and institutional level contribute to doctoral students' attrition rates, with additional issues related to technology and to faculty and peer interaction for online doctoral students (Deshpande, 2016;Lee et al, 2020).…”
Section: Doctoral Educationmentioning
confidence: 99%
“…The experience of graduate students is fundamentally different to that of their undergraduate peers and, thus, requires unique attention and support from higher education leaders, stakeholders, and researchers (Canadian Association for Graduate Studies [Canadian Association for Graduate Studies [CAGS], 2012). Graduate students frequently operate within less structured environments, when compared to undergraduate students who may study within tightly defined course schedules, that require self-motivation and self-directed independent study far in excess of undergraduate programs (Peters, 1997;Owens et al, 2020). In addition, most graduate programs require students to work alongside a supervisor, whose supportiveness (or lack thereof) has been shown to be a predictor of graduate student satisfaction (Dericks et al, 2019;Blanchard & Haccoun, 2020).…”
Section: Graduate Student Experience: a Brief Review Of Literaturementioning
confidence: 99%
“…A limited number of studies focus on the choice to remain in an unhappy supervisory relationship (Barnes et al, 2010;Kulikowski et al, 2019;Al Makhamreh and Stockley, 2019;Owens et al, 2020). Those studies usually focus on "overcoming" and emphasize doctoral students' pride in succeeding despite negative experiences and supervisory problems (Bryan and Guccione, 2018).…”
Section: Introductionmentioning
confidence: 99%